2018
DOI: 10.1021/acssuschemeng.7b04614
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving Oil and Recycling Surfactant in Surfactant-Enhanced Soil Washing

Abstract: How to simultaneously realize retrieving oil and recycling surfactant in the remediation of leaked oil-polluted soil by means of surfactant-enhanced soil washing is still a significant challenge. Here, we reported for the first time a novel CO2-switchable anionic surfactant, 11-dimethylamino-undecyl sulfate sodium salt (DUSNa), to retrieve leaked oil and recycle surfactant simultaneously in the process of oil-polluted sand remediation by DUSNa-enhanced soil washing. Because a CO2-switchable tertiary amine grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…[40] More recently, Xu et al reported a novel CO 2 -switchable anionic surfactant based on a sulfate salt surfactant (i.e., 11-dimethylaminoundecyl sulfate sodium salt, DUSNa) for the oil-contaminated soil remediation (Figure 3b). [41] The authors claimed that the recovery ratio of mineral oil was around 92.1-94.1%, whereas the residual oil on "clean" sands only counted for 2.8-3.2% of the original amount, or less than 0.17% in the aspect of the total mass. Furthermore, the total organic content (TOC) and chemical oxygen demand (COD) in the process water were measured at less than 40 mg L −1 after treatment, indicating excellent decontamination of the process water as well.…”
Section: Switchable Surfactants For Oily Waste Cleanupmentioning
confidence: 99%
See 2 more Smart Citations
“…[40] More recently, Xu et al reported a novel CO 2 -switchable anionic surfactant based on a sulfate salt surfactant (i.e., 11-dimethylaminoundecyl sulfate sodium salt, DUSNa) for the oil-contaminated soil remediation (Figure 3b). [41] The authors claimed that the recovery ratio of mineral oil was around 92.1-94.1%, whereas the residual oil on "clean" sands only counted for 2.8-3.2% of the original amount, or less than 0.17% in the aspect of the total mass. Furthermore, the total organic content (TOC) and chemical oxygen demand (COD) in the process water were measured at less than 40 mg L −1 after treatment, indicating excellent decontamination of the process water as well.…”
Section: Switchable Surfactants For Oily Waste Cleanupmentioning
confidence: 99%
“…Reproduced with permission. [41] Copyright 2018, American Chemical Society.…”
Section: Switchable Polymeric Surfactants For Oil Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Increasingly, more and more people are waking up to that, surfactants are useful in some certain steps, after which they become a liability (Liu et al, 2006). For example, surfactant-enhanced soil washing (SESW) (Ceschia et al, 2014;Xu et al, 2018) is one of the most versatile remediation techniques. In the process of SESW, both the oil-water interfacial tension and the oil-soil attraction are reduced by surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…However, the water insoluble organic contaminants are solubilized or emulsified by surfactants, making it difficult to separate the contaminants from the SESW eluents. It is believed that switchable or stimuli-responsive surfactants may solve this problem (Ceschia et al, 2014;Xu et al, 2018). The reason for this is that switchable surfactants could reversibly interconvert between active and inactive forms under an applicable stimulus.…”
Section: Introductionmentioning
confidence: 99%